Floral Morphogenesis in Euptelea (Eupteleaceae, Ranunculales) - Ren, Yi (Oxford University Press, 2007)
BACKGROUND AND AIMS: Based on molecular phylogenetic studies, the unigeneric family Eupteleaceae has a prominent phylogenetic position at or near the base of Ranunculales, which, in turn, appear at the base of eudicots. The aim of the present paper is to reveal developmental features of the flowers and to put the genus in a morphological context with other basal eudicots. METHODS: Flowers in all developmental stages of Euptelea pleiosperma were collected in the wild at intervals of 7–10 d in the critical stages and studied with a scanning electron microscope. KEY RESULTS: Remnants of a perianth are lacking throughout flower development. Floral symmetry changes from monosymmetric to asymmetric to disymmetric during development. Asymmetry is expressed in that the sequence of stamen initiation is from the centre to both lateral sides on the adaxial side of the flower but starting from one lateral side and proceeding to the other on the abaxial side. Despite the pronounced floral disymmetry, a dimerous pattern of floral organs was not found. The carpel primordia arise between the already large stamens and alternate with them. Stamens and carpels each form a somewhat irregular whorl. The carpels are ascidiate from the beginning. The stigma differentiates as two crests along the ventral slit of the ovary. The few lateral ovules alternate with each other. CONCLUSIONS: Although the flowers have some unusual autapomorphies (wind pollination, lack of a perianth, pronounced disymmetry of the floral base, long connective protrusion, long temporal gap between androecium and gynoecium initiation, small space for carpel initiation), they show some plesiomorphies at the level of basal eudicots (free carpels, basifixed anthers, whorled phyllotaxis), and thus fit well in Ranunculales.